Boron deficiency inhibits petiole and peduncle cell development and reduces growth of cotton - de Oliveira, Rosa Honorato; Dias Milanez, Camilla Rosindo; Moraes-Dallaqua, Marina Aparecida; Rosolem, Ciro Antonio [UNESP] (Taylor & Francis Inc, 2006)
The effect of boron (B) on cotton growth and fruit shedding may be due not only to physiological or biochemical effects, but also to vascular tissue malformation. This experiment investigated petiole and floral peduncle anatomical alterations and growth of cotton supplied with deficient and sufficient B in nutrient solution. Cotton (Gossypium hirsutum cv. 'Delta Opal') plants were grown in solutions containing 0, 1.5, 3.0, 4.5, and 6.0 mu mol L-1 of B from 22 to 36 d after plant emergence (DAPE). From 36 to 51 DAPE, B was omitted from the nutrient solution. Petioles from young leaves and floral bud peduncles (first position of the first sympodial) were sampled and the cross-section anatomy observed under an optical microscope. The number of vascular bundles of the petiole was decreased in B-deficient plants and the xylem was disorganized. Phloem elements in the peduncle vascular cylinder of B-deficient plants did not show clear differentiation. The few xylem elements that were formed were also disorganized. Modifications caused by B deficiency may have impaired B and photosynthate translocation into new cotton growth. Boron accumulation in the shoot of B-deficient plants suggested that there was some B translocation within the plant. It could be inferred that cotton growth would be impaired by the decrease in carbohydrate translocation rather than by B deficiency in the tissue alone.
Keywords: cotton; boron deficiency; xylem; fruit retention; petiole; phloem